(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Lopana Village has an area of ​​4035 Ha and is located approximately 5 km from the Amurang Timur District Government Center, South Minahasa Regency. This community service program aims to provide an understanding of Gout Arthritis disease and the ability of the Elderly (Lansia) to conduct independent Uric Acid level checks. It is hoped that the community can live a healthy lifestyle and be better able to prevent this disease. The Lopana Village Elderly Group is a work group that is very vulnerable to suffering from Gout Arthritis disease and most members have risk factors for Gout Arthritis disease. The method of this activity is to provide health education on Gout Arthritis Disease and how to conduct simple laboratory tests independently. The results of this activity show an increase in understanding of gout arthritis disease and the ability of the Elderly and the PKK Team to conduct independent uric acid level checks. The conclusion of this activity is that in male participants there was an increase in knowledge from 40% (before health education) to 90% (after health education). In female participants there was an increase in knowledge from 60% (before health education) to 100% (after health education).